Oral Cancer Metastasis - Myers, Jeffrey (Springer New York : Imprint: Springer, 2010)
Squamous cell carcinoma of the oral cavity (SCCOC) is one of the most prevalent tumors of the head and neck region. Despite improvements in treatment, the survival of patients with SCCOC has not significantly improved over the past several decades. Most frequently, treatment failure takes the form of local and regional recurrences, but as disease control in these areas improves, SCCOC treatment failures more commonly occur as distant metastasis. This book summarizes the current status of investigations into SCCOC metastases and potential of these studies to positively impact clinical management of SCCOC in the future.